Genome‐wide analysis identifies novel genetic variants and unique biological pathways associated with AD‐related proteins in the brain. (1st February 2022) - Oatman, Stephanie R; Reddy, Joseph S.; Quicksall, Zachary; Carrasquillo, Minerva M.; Wang, Xue; Liu, Chia‐Chen; Yamazaki, Yu; Nguyen, Thuy; Malphrus, Kimberly G.; Heckman, Michael G.; Martens, Yuka A; Zhao, Na; et al.
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder neuropathologically characterized by amyloid‐β (Aβ) plaques and neurofibrillary tangles. Assessment of AD‐related endophenotypes can reveal novel insights into aspects of the heterogeneity of AD. We hypothesize that, amongst AD patients, the levels and solubility of AD‐related proteins are influenced by genetic variants; identifying these may provide key insights into disease pathogenesis. To test this, we performed a genome‐wide association study (GWAS) for the levels of five AD‐related proteins (apoE, Aβ40, Aβ42, tau, and p‐tau) in the brain. Methods: Genome‐wide genotypes were collected from 441 autopsy‐confirmed AD cases on the Infinium Omni2.5Exome‐8 v1.3 genotyping array, imputed to the haplotype reference consortium (HRC) panel, and quality filtered. Temporal cortex levels of the five AD‐related proteins from three fractions, i.e. buffer‐soluble (TBS), detergent‐soluble (Triton‐X=TX), and insoluble (Formic acid=FA) were measured by ELISA. Using linear regression, genetic variants were tested for association with each biochemical measure, and the Aβ40/42 ratio. Pathway analysis was done using GSA‐SNP2 to identify enriched Gene Ontology (GO) terms. Results: We identified 9 unique GWS variants (genome‐wide significant, p<2.89E‐08), 2 at the APOE locus and 7 novel. Variants within the APOE locus were significantly associated with Aβ40 levels in the TX and FA fractions, the Aβ40/42 ratio in the FA fraction, and apoE levels in the TBS and FA fractions. Of the novel GWS variants, four were associated with Aβ40 residing on chromosomes 17 (TBS), 3, 4, and 15 (TX), and three with apoE levels on chromosomes 19 (TBS), 7, and 14 (TX). Pathway analysis revealed both shared and distinct pathways significantly enriched for the GWAS results. Conclusions: Although all biochemical measures tested reflect proteins core to AD pathology, our results strongly suggest each have unique genetic factors and enriched pathways which influence their brain levels. Furthermore, discovery of genetic factors that underlie specific biochemical outcomes may lead to the identification of novel genes that influence biochemical properties of AD proteins. These findings can enhance our understanding of the pathophysiology of proteostasis in AD and may have implications for other neurodegenerative diseases also characterized by abnormal protein accumulation in the brain.